Semiconductor oxide for gas sensing applications - Ang, Wan Chia (2010)
The semiconductor metal oxide oxygen sensors have received the most attention during the past few years due to their advantages of low cost, small size, simple structure, and the ease of integration. In this project, SrTi1−x FexO3−δ (STFx, 0 ≤ x ≤ 1) was used as the material for oxygen sensing application. The STFx thin films and composite films were developed by using modified sol-gel spin-coating technique. STFx sol-gel solutions with varying iron content were prepared and examined prior to deposition of STFx thin films and composite films. Effects of sol molarity, water content, and amount of PVP added into the STFx sol-gel solutions were studied and investigated in order to obtain stable solution and uniform spin-coated thin films. The surface morphology of the spin-coated thin films was characterized using FESEM and AFM. Next, the effect of annealing temperature on thin film grain size and crystallization was studied using XRD and the optimum annealing temperature was chosen for gas sensing device fabrication. On the other hand, STF02 composite films were obtained by dispersing the STF02 nanoparticles in STF02 sol-gel solutions. STF02 nanoparticles were synthesized using high energy ball milling technique. Particle size and dispersion of STF02 nanoparticles were then investigated using Zeta sizer test. Slurry preparation procedure was revised to obtain stable and well dispersed STF02 slurry. The STF02 sol-gel solution recipe for slurry preparation was modified by adding PVP in order to reduce cracks formation. The optimum amounts of PVP and powder-to-sol weight ratios were investigated to obtain crack-free composite film. Surface morphology of the spin-coated composite films was studied using SEM. In gas sensing device fabrication process, STF04 thin film was spin-coated onto the SiO2 wafer substrate with gold bottom interdigitated electrodes and patterned using photolithography technique. Next, gas sensing characterization was carried out by using home-designed gas sensor characterization system (GSCS). The STF04 gas sensing devices showed excellent oxygen sensing response. The annealing temperature and PVP addition effect on the devices sensing response were characterized and evaluated.